Critical series

Calculus Level 3

1 + 2 1 3 2 + 2 5 1 2 1 3 4 + 2 5 8 1 2 3 1 3 6 + = ? \large 1+2\cdot \frac{1}{3^2}+\frac{2\cdot 5}{1\cdot 2}\cdot \frac{1}{3^4}+\frac{2\cdot 5\cdot 8}{1\cdot 2\cdot 3}\cdot \frac{1}{3^6}+\cdots = ?

1 3 \frac{1}{\sqrt3} Can't be determined 9 4 3 \sqrt[3]{\frac{9}{4}} 1 2 \frac{1}{\sqrt2} 2 3 \sqrt[3]{2} None of them

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Let S S be the sum given. Consider the Taylor series centered around x = 0 x=0 of 1 + x 3 \sqrt[3]{1+x} :

1 + x 3 = 1 + x 3 2 x 2 2 ! 3 2 + 2 5 x 3 3 ! 3 3 2 5 8 x 4 4 ! 3 4 + Differentiate both side w.r.t. x 1 3 ( 1 + x ) 2 3 = 1 3 2 x 1 ! 3 2 + 2 5 x 2 2 ! 3 3 2 5 8 x 3 3 ! 3 4 + Multiply both side by 3 ( 1 + x ) 2 3 = 1 2 x 1 ! 3 + 2 5 x 2 2 ! 3 2 2 5 8 x 3 3 ! 3 3 + Put x = 1 3 ( 1 1 3 ) 2 3 = 1 + 2 1 ! 3 2 + 2 5 2 ! 3 4 + 2 5 8 3 ! 3 6 + \begin{aligned} \sqrt[3]{1+x} & = 1 + \frac x3 - \frac {2x^2}{2!3^2} + \frac {2\cdot 5 x^3}{3!3^3} - \frac {2\cdot 5 \cdot 8 x^4}{4!3^4} + \cdots & \small \color{#3D99F6} \text{Differentiate both side w.r.t. }x \\ \frac 13 (1+x)^{-\frac 23} & = \frac 13 - \frac {2x}{1!3^2} + \frac {2\cdot 5 x^2}{2!3^3} - \frac {2\cdot 5 \cdot 8 x^3}{3!3^4} + \cdots & \small \color{#3D99F6} \text{Multiply both side by }3 \\ (1+x)^{-\frac 23} & = 1 - \frac {2x}{1!3} + \frac {2\cdot 5 x^2}{2!3^2} - \frac {2\cdot 5 \cdot 8 x^3}{3!3^3} + \cdots & \small \color{#3D99F6} \text{Put } x = - \frac 13 \\ \left(1-\frac 13\right)^{-\frac 23} & = 1 +\frac {2}{1!3^2} + \frac {2\cdot 5}{2!3^4} + \frac {2\cdot 5 \cdot 8}{3!3^6} + \cdots \end{aligned}

S = ( 1 1 3 ) 2 3 = ( 3 2 ) 2 3 = 9 4 3 \begin{aligned} \implies S & = \left(1-\frac 13\right)^{-\frac 23} = \left(\frac 32\right)^\frac 23 = \boxed{\sqrt[3]{\dfrac 94}} \end{aligned}

Masbahul Islam
Nov 28, 2017

n=-2/3

x=-1/3

(1-x)^n =(9/4)^(1/3)

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...